CULTURAL IMPACT ON COMMITMENT TO CHANGE OF LOWER LEVEL EMPLOYEES - Ekanayake, Isuru Achintha; Kumari, Rathnayaka Mudiyanselage Samanthika; Nimalsiri, Sachini Charuni (PEOPLE: International Journal of Social Sciences, 2019)
Many efforts for successful implementation of planned changes have fail due to various reasons; out of which people factor is crucial. Thus, managing a change is a challenge. Hence the present study considered commitment to change of lower level employees in Sri Lankan context. The research was based on two studies; first, to find out the levels of commitment to change; and second, to find out the relationship between commitment to change and two cultural dimensions; power distance and individualism using a survey method. The findings revealed that, lower level employees have less affective and normative commitment to change while high continuance commitment to change. Both power distance and individualism significantly and negatively correlated with commitment to change. Thus, lower level employees expect a less power distant and collective work culture to support a successful change effort.